The Well-being and Support Needs of Australian Caregivers of Neurodiverse Children - D’Arcy, Emily; Burnett, Tayah; Capstick, Emily; Elder, Catherine; Slee, Olivia; Girdler, Sonya; Scott, Melissa; Milbourn, Ben (2023)
Caregivers of children with neurodiverse needs are known to experience challenges and hardship due to the increased needs of the child and the lack of support available. This study aimed to explore the support needs and well-being of caregivers of children with neurodiverse needs in Australia. Sixty-six caregivers participated in an online survey asking questions about support needs. The results highlighted five main themes that caregivers commonly experienced including: barriers to community engagement, impact on close relationships, negative impact on mental health and identity, financial hardship, and identified support needs. Findings identified multiple unmet needs existing amongst caregivers and further emphasises the importance of addressing these needs to improve the quality of life of caregivers of children with neurodiverse needs.